Application of TQM to road races: Study on the sports involvement and willingness to re-participate - Wu Chao-Sen (Cogent Business & Management, 2018)
This study mainly explored the application of total quality management (TQM) to road running competitions, as well as the correlation and influence between the involvement and willingness of re-participation of road runners. This study conducted questionnaire survey and regarded road runners as its subjects. Hence, the recovery rate was 86.91%. The results show that the involvement of road runners will enhance their willingness of re-participation. Furthermore, involvement has a positive and significant influence on TQM. TQM has a positive and significant influence on willingness of re-participation. Then, this study verified the correlation among involvement, TQM, and willingness of re-participation and concluded that TQM serves an intermediary role among the three variables. To sum up, strengthened quality management of competitions and the involvement of runners can attract the attention of the public, create positive value of road running, and improve the recognition of runners to road race. Through the creation of value of road running, road running competition organizers shall introduce the benefits of TQM, strengthen the quality of service, enhance the effectiveness of competitions, and prevent emergencies, which will increase the satisfaction of road runners and event participants with the overall events.
Keywords: 650